Development of a high-gain deployable S-band antenna for small satellite data transmission - Zhao, Manli (Nanyang Technological University, 2021)
In recent years, the world of small satellites has seen rapid evolution, bringing forth an opportunity to leverage these developments for the purpose of scientific progress. One of the biggest challenges in a small satellite is the transmission of payload data. The amount of data transferred is dependent on the frequency, with a higher frequency providing a higher bandwidth that can support higher data rates being preferred but with the trade-off of larger power consumption. Hence, the design of the small satellites' communication subsystems is of vital importance.